Donor lymphocyte infusion leads to diversity of specific T cell responses and reduces regulatory T cell frequency in clinical responders. Issue 5 (27th September 2018) - Hofmann, Susanne; Schmitt, Michael; Götz, Marlies; Döhner, Hartmut; Wiesneth, Markus; Bunjes, Donald; Greiner, Jochen
Abstract : T cell responses against malignant cells play a major role in maintaining remission and prolonging overall survival in patients after allogeneic stem cell transplantation and donor lymphocyte infusion (DLI) due to graft‐versus‐leukemia effect. For better characterization of the T cell responses, we assessed frequency and diversity of leukemia‐associated antigen (LAA)‐specific cytotoxic T cells using ELISpot and pMHC multimer assays and analyzed the frequency of regulatory T cells (Treg) as well as cytokine profiles before/after DLI. The data were correlated to the clinical course of patients. Significantly more LAA‐derived T cell epitopes ( p = 0.02) were recognized in clinical responders (R) when compared to nonresponders (NR). In addition, pMHC multimer‐based flow cytometry showed a significantly higher frequency of LAA‐specific T cells in R versus NR. The frequency of Treg in R decreased significantly ( p = 0.008) while keeping stable in NR. No differences in T cell subset analysis before/after DLI were revealed. Clinical responders were correlated to specific immune responses and all clinical responders showed an increase of specific immune responses after DLI. Cytokine assays using enzyme‐linked immunosorbent assay showed a significant increase of IL‐4 after DLI. Taken together, an increase of specific CTL responses against several LAA after DLI was detected. Moreover, this study suggests that enhanced LAA diversity in T cell responses as well as decreasing numbers of Treg contribute to clinical outcome of patients treated with DLI. Abstract : What's new? Donor lymphocyte infusion (DLI) bears curative potential for leukemia patients due to the graft‐versus‐leukemia (GvL)‐effect, but it may also cause life‐threatening graft‐versus‐host disease (GvHD). A better understanding of specific T cell responses would help increase GvL potency without raising the risk of GvHD. Here, the authors assessed the frequency and diversity of leukemia‐associated antigen (LAA)‐specific cytotoxic T cells in 11 patients. An increase in specific CTL responses against several LAA following DLI was detected. The enhanced LAA diversity in T cell responses and the decreasing number of regulatory T cells may contribute to the clinical outcome of DLI treated patients.